Microbiome Community Structure and Functional Gene Partitioning in Different Micro-Niches Within a Sporocarp-Forming Fungus - Liu, Dong; He, Xinhua; Chater, Caspar C. C.; Perez-Moreno, Jesús; Yu, Fuqiang (Frontiers in Microbiology, 2021)
Thelephora ganbajun is a wild edible mushroom highly appreciated throughout China. The microbiomes of some fungal basidiomata have been studied, however their potential functional roles currently remain uncharacterized. Here, functional gene microarrays (GeoChip 5.0) and amplicon sequencing were employed to define the taxonomic and functional attributes within three micro-niches of T. ganbajun. The diversity and composition of bacterial taxa and their functional genes differed significantly (p < 0.01) among the compartments. Among 31,117 functional genes detected, some were exclusively recorded in one basidioma compartment: 1,334 genes involved in carbon (mdh) and nitrogen fixation (nifH) in the context; 524 genes influencing carbon (apu) and sulfite reduction (dsrB, dsra) in the hymenophore; and 255 genes involved in sulfur oxidation (soxB and soxC) and polyphosphate degradation (ppx) in the pileipellis. These results shed light on a previously unknown microbiome and functional gene partitioning in sporome compartments of Basidiomycota. This also has great implications for their potential ecological and biogeochemical functions, demonstrating a higher genomic complexity than previously thought.